AGE Survey: a Tool to Support the Study and Intervention on Health and Age at Work - Ramos, S.; Mardon, .; Carvalho, H. (13th European Academy of Occupational Health Psychology Conference, 2018)
The complex relationship between age and work goes beyond the association between the exposure to risk factors and early ageing. Only few studies attempt to encompass this complexity and try to put this discussion in a temporal dimension, considering the developments of health and work over lifetime. This proposal presents some results of a study conducted in Portugal about working conditions, occupational risks and health problems. European studies, as ESTEV and VISAT, both in France, used a longitudinal design with repeated measures in order to monitor health issues taking into account job modifications and age evolution. From these experiences, other studies were performed in this field, with less extensive instruments, for example the SVP50 and EVREST. In Portugal we developed the first survey on health and age – AGE– based on the previous experiences and supported by the strong network between researchers from these groups. The first AGE data collection was conducted in 2016, in collaboration with the National Authority for Working Conditions. The survey was administrated by labour inspectors in their regular visits to companies, with 3106 surveyed workers. AGE dimensions focus on: working conditions (working time, schedules, demands/resources, perceived risks); health complaints and the perceived (by workers) relationship between these problems and their work, in order to analyse the relationship between age, health and work; and questions about retirement expectations, in order to identify retirement predictors. The results show interesting relations between working conditions and the health problems identified by workers and, with strong evidences that age plays a key role in the capacity to recognise the connection between work constraints and health problems. Results also show different tendencies related to both perceived expositions and perceived health problems for different age groups, emphasising the need to consider the specificity of diverse situations in the moment of intervention. Findings also show that these health problems are frequently reported by workers, as related to their work, mostly in work situations of co-exposition (when workers are exposed to several constrains at the same time). The association of different constraints seem to be particularly hard for workers, due to the high proportion of reported health problems.